Acute squares of colonic diverticular origin - Mautone, Daniel; Salgado, Moisés (Cirugía del Uruguay, 1970)
Colonic diverticular urgences are described. In acute syndroms of the left lower quadrant of the abdomen, prevention is made about detection of other complications ( abcess, obstruction, perforation) that may be presents, exeding the common conservative treatment, considered generally -effective, but not infallible. Right side acute diverticular syndroms are after described. Generally diagnosticated as appendicitis. A case simulating . colecistitis and other diagnosticated cancer of the coecum are related. Diffuse peritonitis is considered the most important cause of mortality from -colonic diverticular disease. Different types of perforation and peritonitis according to original colopaty are considered, and surgical recurses and tactics described. Recommendation is made about use of adecuate and not systematic tactics. The obstructive diverticular syndrom is described according to original phisiopaihologic factors. Investigations of these factors is especially recommended. Abcess and peritonitis must be detected always, to be treated opportunally. Management of yeyunoileal obstruction is described. Possibility of carcinoma is considered in all acute colonic obstruction in a diverticular patient. · Ethiopathogenic and diagnostic dates on mas.sive diverticular hemorrhage are reviewed and surgical recurses discussed. Tactical management is described. Ten operated and demonstrative .cases are related. Were employed different proceedings that include minimal to radical and complex recurses, according to presents ci rcunstances.